Relationship between multimorbidity treatment burden and chronic disease self-efficacy in the elderly population of China - Guo, Yiwei; Tan, Jialong; Shi, Weigui; Bai, Jing; Wang, Jian (Frontiers in Medicine, 2025)
ObjectivesThis study aimed to evaluate the risk factors associated with the treatment burden of multimorbidity among older Chinese adults and to investigate the relationship between treatment burden and chronic disease self-efficacy.MethodsData for this study were collected from a population-based investigation of individuals aged 60 years and older with at least two chronic diseases, conducted by Wuhan University. A structured questionnaire was employed to collect demographic information, chronic disease status, multimorbidity treatment burden (assessed using the Multimorbidity Treatment Burden Questionnaire, MTBQ), and chronic disease self-efficacy (assessed using the Self-Efficacy for Managing Chronic Disease 6-item scale, SEMCD6). The Pearson chi-square test and logistic regression were used to analyze the data.ResultsA total of 1,599 individuals with a mean age of 71.48 years were enrolled in our study, of whom 13.01% were over 80 years. The proportion of low, medium, and high multimorbidity treatment burden was 30.42, 13.88, and 15.21%, respectively. For elderly individuals; residence; gender; age; high school education experience; comorbidities with stroke, chronic respiratory disease, Parkinson’s disease, dementia, psychological disorders; and individuals who had 6 or more chronic diseases were found to be significantly associated with the MTBQ score. A higher MTBQ score was significantly associated with a lower SEMCD6 score.ConclusionThe findings suggest that lower socioeconomic status and comorbidities with stroke, cognitive diseases, and mental disorders contribute to a higher perceived MTBQ score. Moreover, a higher level of multimorbidity treatment burden may potentially lead to poorer motivation for health management behaviors.